Ontology-based Knowledge Modeling of Post-occupancy Evaluation for Green Building. Issue 1 (April 2020) - Zhao, Yuanhong; Yang, Qingping; Fox, Andrew; Zhang, Tao
Abstract: Despite the development of advanced information and knowledge management technologies in the architecture, engineering, and construction (AEC) industry, there is still a missing link between the green building performance evaluation (BPE) domain and the knowledge management system. In the BPE domain, post-occupancy evaluation (POE) has been developed as an effective method to evaluate actual building performance after the building has been occupied for some time. However, the vast POE knowledge is mostly documented in various standardized references with different focuses, and it is time-consuming to manage and acquire scattered and fragmented knowledge data. Ontology, as a semantic web technology, has been widely used in the knowledge representation and management engineering field. Hence, this research integrates ontology into the green building post-occupancy assessment domain to develop a unified semantic model to systematize the fragmented knowledge. The extracted POE knowledge from evaluation standards is formalized into OWL (Ontology Web Language) ontology, which achieves knowledge systematization in the POE domain and enables the knowledge-based application systems to retrieve, share and reuse POE knowledge more effectively.